Dynamic dispersing technique for PR coating process in planar lightwave circuit fabrication - Pua, Chang Hong; Harun, Sulaiman Wadi; Chong, Wu Yi; Jayapalan, Kanesh Kumar; Ahmad, Harith (John Wiley & Sons, 2007)
A new dynamic dispersing technique (DDT) is proposed and demonstrated to improve the photoresist (PR) coating process in planar lightwave circuit (PLC) fabrication. In this technique, the PR is dispensed during the wafer's spin cycle on the spin coaler instead of the conventional static dispensing before spinning. In comparison to the conventional static dispersing technique (SDT), DDT has significantly improved several properties of the PR layer including its thinning behavior, coating uniformity, and PR amount. Using DDT, the PR thickness averagely reduces by -0.2 μm. The radial uniformity of the PR from the centre is also improved from the average difference of 0.28 μm in SDT to 0.14 μm in DDT. Furthermore, the PR amount required for the coating process is reduced from 3.00 ml (SDT) to 0.25 ml (DDT). Two different DDTs are also compared in this paper including the application of PR during the spin cooler's acceleration step (Ist DDT) and the application of PR during the spin coaler's constant speed (2nd DDT).